School desruralization: a study on the closure of rural schools in a municipality of the State of Rio de Janeiro - Vanessa Lima Sanches; Marcia Lisbôa Costa de Oliveira (Universidade Federal do Norte do Tocantins, 2019)
This paper presents a study about the deactivation and the extinction of rural schools located in the municipality of Cachoeiras de Macacu (Rio de Janeiro State Metropolitan Region), focusing on the impact of the construction of the Guapiaçu River dam in this process. The data analyzed show that in the rural region of Cachoeiras de Macacu, between 1983 and 2016, 35 schools were deactivated or extinguished, of which 8 were administered by the state and 27 by the municipality. Starting from the discussion of the changing of the population profile and the perimetropolization of the municipality, we analyze the school desruralization process. We noticed that the transportation of students to urban areas constitutes an administrative strategy for school "optimization" and that the Guapiaçu River dam project accentuated this orientation in the Serra Queimada region. Considering that "the identity of the rural school is defined by its connection with the issues inherent to its reality" (Brazil, 2012), we understand that the closure of rural schools indicates the invisibility of peasant populations, whose knowledge and way of life are taken as nonexistent. In this way, they are radically excluded from civil society (Santos, 2007).